Aplicación de la música y literatura en el proceso creativo gastronómico - Chávez Cuesta, Giovanni Sebastián (2019)
Music and literature are two types of art that go hand in hand. From the very conception of literature, music plays an important role and vice versa. Within a gastronomic experience, music and literature are fundamental pieces because they help maximize the senses of the guests. Each one of the seven arts depends on the other six to be conceived, created and applied in the different artistic development platforms. In this case, music and literature are created with the intention of extending the different sensory experiences of each person who consumes this type of art, likewise, gastronomy extends these perceptions to improve the experience. In this way, we can pick up the culinary artistic branch of gastronomy and be able to apply the two previously mentioned arts to amplify their concept and conception from their creative process. Because art is printed in the subjectivity of those who consume it, this research has sought common denominators and different creative processes to be able to apply them and link them with gastronomy. In this research work, two techniques were applied: the reception of bibliographic information and the different testimonies of an expert in each of the mentioned areas. After this inquiry, an analysis has been made that is presented in this thesis with a manifesto of the application of music and literature in the culinary creative process.